Análise das vantagens da implementação de um escritório de projetos dentro de uma empresa prestadora de serviços de TI - Balbinot, Guilherme Carneiro (Universidade do Vale do Rio dos Sinos, 2016)
The project development and project management discipline in the IT field is increasing, especially for companies that provide service in this area. It is justified due to high competition between companies and the level of control they need to have on your project portfolio. Thus arises the need for implementation of a project management office (PMO). This paper presents a survey of a provider of IT services through a practical methodology. It is intended to present the advantages that the company can get on with the implementation of the project office through a literature study, analysis of your current process and a practical application of the PMO VALUE RING tool. As a result, the ideal type of PMO and its core services that must be implemented cyclically, according to the real needs of the company was identified. During the research, it was also possible to define a new project management methodology for the company and develop a standard documentation, according to the best market practices.
Keywords: Gerenciamento de projetos; Portfólio de projetos; Escritório de projetos; Project management; Project portfolio; Project office